Vitamin D receptor agonist EB1089 is a potent regulator of prostatic "intracrine" metabolism. Issue 3 (February 2014) - Doherty, Declan; Dvorkin, Scarlett Anne; Rodriguez, Edna Patricia; Thompson, Paul Daniel
Abstract BACKGROUND A contributing factor to the emergence of castrate resistant prostate cancer (CRPC) is the ability of the tumor to circumvent low circulating levels of testosterone during androgen deprivation therapy (ADT), through the production of "intracrine" tumoral androgens from precursors including cholesterol and dehydroepiandrosterone (DHEA). As these processes promote AR signaling and prostate cancer progression their modulation is required for disease prevention and treatment. METHODS We evaluated the involvement of the vitamin D receptor ligand EB1089 in the regulation of genes with a role in androgen metabolism using the androgen dependent cell lines LNCaP and LAPC‐4. EB1089 regulation of androgen metabolism was assessed using QRT‐PCR, luciferase promoter assays, western blotting, enzyme activity assays, and LC–MS analyses. RESULTS EB1089 induced significant expression of genes involved in androgen metabolism in prostate cancer cells. Real‐Time PCR analysis revealed that VDR mediated significant regulation of CYP3A4, CYP3A5, CYP3A43, AKR1C1‐3, UGT2B15/17, and HSD17B2. Data revealed potent regulation of CYP3A4 at the level of mRNA, protein expression and enzymatic activity, with VDR identified as the predominant regulator. Inhibition of CYP3A activity using the specific inhibitor ritonavir resulted in alleviation of the anti‐proliferative response of VDR ligands in prostate cancer cells. Mass spectrometry revealed that overexpression of CYP3A protein in prostate cancer cells resulted in a significant increase in the oxidative inactivation of testosterone and DHEA to their 6‐β‐hydroxy‐testosterone and 16‐α‐hydroxy‐DHEA metabolites, respectively. CONCLUSIONS These data highlight a potential application of VDR‐based therapies for the reduction of growth‐promoting androgens within the tumor micro‐environment. Prostate 74:273–285, 2014. © 2013 Wiley Periodicals, Inc.